2007
DOI: 10.1108/17479894200700011
|View full text |Cite
|
Sign up to set email alerts
|

‘I was Independent since I was Born’: Pre‐Immigration Traumatic Experiences and Pathological Gambling in Four Chinese Canadians

Abstract: Trauma and adverse childhood events are found in the pre-immigration histories of a cohort of four Chinese Canadian pathological gamblers. The nature of their traumatic experiences, consisting of loss and abandonment, neglect and deprivation, physical and emotional abuse, socioeconomic and political oppression, is elucidated and described. The impact of pre-immigration trauma and its relationship to the development of pathological gambling post-immigration are discussed. Upon further corroboration of the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The study's findings illuminate the importance of understanding both the individual and family perspectives, a point made by numerous authors (Abbott, 1999(Abbott, , 2001Dickson-Swift et al, 2005;Grant & Won Kim, 2002;Grant Kalischuk et al, 2006). Increasing awareness about the importance of involving as many family members as possible in the delivery of family-focused treatment is recommended, an approach supported by other researchers (Dickson-Swift et al, 2005Lee et al, 2007.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The study's findings illuminate the importance of understanding both the individual and family perspectives, a point made by numerous authors (Abbott, 1999(Abbott, , 2001Dickson-Swift et al, 2005;Grant & Won Kim, 2002;Grant Kalischuk et al, 2006). Increasing awareness about the importance of involving as many family members as possible in the delivery of family-focused treatment is recommended, an approach supported by other researchers (Dickson-Swift et al, 2005Lee et al, 2007.…”
Section: Discussionsupporting
confidence: 53%
“…Upon further corroboration of the existence of trauma among VLT problem gamblers in future studies, it is imperative that addictions counselors and health care and social service professionals be provided with educational opportunities that enable them to acquire a skill set for sensitively and effectively working with individuals who have been traumatized by various types of losses. Echoing the viewpoint of other researchers (Kausch et al, 2006;Lee, Solowoniuk, & Fong, 2007), multidisciplinary education that prepares professionals for effectively working with traumatized individuals and their families is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…An in‐depth qualitative study of a Chinese Canadian sample revealed similar findings of pre‐existing couple fault‐lines and discord before problem gambling onset, decreasing relational resilience over time post‐migration, pathological gambling development around life transitions and setbacks, a history of childhood trauma among gamblers and the use of pathological gambling to assuage a dysphoric mood (Lee et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…Storr et al [ 27 ] and Lee et al [ 28 ] reported that youth who participated in gambling activities experienced more adverse life events such as threats of harm, violence or deviant activity. Research shows that there is an association between childhood experiences of trauma and adversity and adult problem gambling [ 29 , 30 , 31 , 32 ]. A case study by Lee, Solowoniuk and Fong [ 30 ] found that both substance use and childhood adversity (including childhood maltreatment) were associated with problem gambling among male and female adults.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that there is an association between childhood experiences of trauma and adversity and adult problem gambling [ 29 , 30 , 31 , 32 ]. A case study by Lee, Solowoniuk and Fong [ 30 ] found that both substance use and childhood adversity (including childhood maltreatment) were associated with problem gambling among male and female adults. More recently, Saugeres et al [ 33 ] found that childhood experiences of family dysfunction and gambling in the family contributed to adult problematic gambling.…”
Section: Introductionmentioning
confidence: 99%